Slug, Twist, and E-Cadherin as Immunohistochemical Biomarkers in Meningeal Tumors - Nagaishi, Masaya (Public Library of Science, 2012)
The overexpression of Twist and Slug and subsequent down-regulation of E-cadherin facilitate the acquirement of invasive growth properties in cancer cells. It is unclear which of these molecules are expressed in mesenchymal tumors in the central nervous system. Here, we investigated 10 cases each of hemangiopericytoma, solitary fibrous tumor, meningothelial, fibrous, angiomatous, and atypical meningiomas, and 5 cases of anaplastic meningioma for Slug, Twist, E-cadherin, and N-cadherin immunoexpression. Nuclear Slug expression was observed in 9/10 (90%) hemangiopericytomas and 5/10 (50%) solitary fibrous tumors, but not in any meningiomas, except for 1 case. Similarly, nuclear Twist expression was more extensive in hemangiopericytomas and solitary fibrous tumors than meningiomas. In contrast to Slug and Twist, the positive expression of E-cadherin was observed in 39/45 (87%) meningiomas, but not in any hemangiopericytomas or solitary fibrous tumors (P<0.0001). The fraction of tumor cells expressing E-cadherin in meningeal tumors was negatively correlated to those of Twist (P = 0.004) and Slug (P<0.0001). The overexpression of Slug and Twist with down-regulation of E-cadherin was characteristic findings in hemangiopericytomas and solitary fibrous tumors, but not in meningiomas. The immunohistochemical profiles of the two tumor groups may be useful as diagnostic markers in cases that present a differential diagnosis challenge.